On the Statistics and Geography of the Polish Press in the Period between the Uprisings (1832-1864) - Kolasa, Władysław Marek (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2016)
This article presents a brief description of the Polish press and its development during the years 1832-1864. The main objective of this study is to precisely define the press’s quantitative growth and territorial distribution. The source of the study was data obtained from the analysis of all (including the most recent) documentary sources. As a result of the research, it was established that during the years 1832-1864 on the Polish lands and abroad, 626 press titles were published, out of which 185 were issued in the Russian Partition, 161 in the Austrian sector, 130 in the Prussian sector, and 150 abroad. The study also presents the main areas of qualitative transformation (typology, journalistic skills, organisation of the editorial office) and selected determinants shaping the development of the press market in the years 1832-1864 (legal, political, economic impulses). The study is concluded by a brief comparative analysis, where the press of the period between Uprisings is analysed as compared to the development of the Polish press in the years 1729-1819. The analysis indicates that until the mid-nineteenth century, the Polish press had been in its initial period of development. Rapid quantitative and qualitative changes in the press took place only in the last two decades of the nineteenth century and the first decade of the twentieth century.